The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1108/jima-09-2019-0183
|View full text |Cite
|
Sign up to set email alerts
|

Relationship dynamics in customer loyalty to online banking services

Abstract: Purpose The purpose of this paper is to investigate the effect of service quality and relationship quality on customer loyalty in different stages of the relationship life cycle in online banking services. Design/methodology/approach A total of 651 Iranian online banking customers participated in the research by completing questionnaires. The research hypotheses were tested using structural modeling technique. Findings The results showed that the relationship quality on customer loyalty in online banking s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 167 publications
(282 reference statements)
0
13
0
7
Order By: Relevance
“…Moreover, studies conducted by Yi and La (2004) and Sreeram et al, (2017) also found out that customer satisfaction had a positive impact on loyalty. Further research by Lam and Barton (2006), Ball et al, (2006), Yap et al, (2012) and Garepasha et al, (2021) also found out that in the mobile banking industry, satisfaction positively impacted customer loyalty. The basic concept regarding the relationships between customer satisfaction and loyalty has been one of the most studied and discussed concepts within the modern marketing context in the 21st century.…”
Section: Impact Of Customer Satisfaction On Customer Loyaltymentioning
confidence: 96%
“…Moreover, studies conducted by Yi and La (2004) and Sreeram et al, (2017) also found out that customer satisfaction had a positive impact on loyalty. Further research by Lam and Barton (2006), Ball et al, (2006), Yap et al, (2012) and Garepasha et al, (2021) also found out that in the mobile banking industry, satisfaction positively impacted customer loyalty. The basic concept regarding the relationships between customer satisfaction and loyalty has been one of the most studied and discussed concepts within the modern marketing context in the 21st century.…”
Section: Impact Of Customer Satisfaction On Customer Loyaltymentioning
confidence: 96%
“…Thus, better service quality is likely to keep customers loyal. Haron et al (2020) and Garepasha et al (2020) use Malaysian and Iranian Islamic banking data to ascertain that service quality positively affects customer loyalty. They recommend that Islamic banking staff should be polite, professional, and pay more attention to delivering appropriate financial advice for easy access to account information.…”
Section: Service Qualitymentioning
confidence: 99%
“…They noted that these constructs are related to the users' psychological cognition that can further enhance consumer usage of internet banking. Furthermore, according to Akram Garepasha et al (2020), management in the banking industry needs to consider these factors to ensure that customers remain loyal towards internet banking. In their research among internet banking users, they further concluded that trust and commiAtment have shown a positive impact on customer loyalty.…”
Section: Literature Reviewmentioning
confidence: 99%